Li-Rich Antiperovskite/Nitrile Butadiene Rubber Composite Electrolyte for Sheet-Type Solid-State Lithium Metal Battery - Bian, Juncao; Yuan, Huimin; Li, Muqing; Ling, Sifan; Deng, Bei; Luo, Wen; Chen, Xuedan; Yin, Lihong; Li, Shuai; Kong, Long; Zhao, Ruo; Lin, Haibin; et al. (Frontiers in Chemistry, 2021)
Lithium-rich antiperovskites (LiRAPs) holds great promise to be the choice of solid-state electrolytes (SSEs) owing to their high ionic conductivity, low activation energy and low cost. However, processing sheet-type solid-state Li metal batteries (SSLiB) with LiRAPs remains challenging due to the lack of robust technique for battery processing. Herein, we propose a scalable slurry-based procedure to prepare a flexible composite electrolyte (CPE), in which LiRAP (e.g. Li2OHCl0.5Br0.5, LOCB) and nitrile butadiene rubber (NBR) serve as an active filler and as a polymer scaffold, respectively. The low-polar solvent helps to stabilize the LiRAP phase during slurry processing. It is found that the addition of LOCB into the NBR polymer enhances the Li ion conductivity for 2.3 times at 60 ℃ and reduces the activation energy (max. 0.07 eV). The as-prepared LOCB /NBR CPE film exhibits an improved critical current of 0.4 mA cm-2 and can stably cycle for over 1000 h at 0.04 mA cm-2 under 60 ℃. In the SSLiB with the sheet-type configuration of LiFePO4(LFP)||LOCB /NBR CPE||Li, LFP exhibits a capacity of 137 mAh g-1 under 60℃ at 0.1C. This work delivers an effective strategy for fabrication of LiRAP based CPE film, advancing the LiRAP-family SSEs towards practical applications.